Evaluation of dahi collected from Netrokona district in Bangladesh (Bangladesh Journal of Animal Science, 2016)
The aim of the present research work was to make a comparative study between the quality of dahi available in Netrokona district of Bangladesh and dahi prepared in the laboratory by following standard manufacturing process. For this purpose dahi (control) was prepared in Dairy Technology Laboratory of the Department of dairy science, Bangladesh Agricultural University, Mymensingh. The Laboratory made dahi was designated as A type dahi. On the other hand four different types of dahi sample were collected from four different sweetmeat shop of Netrokona district. One sample was taken from each sweetmeat shop and three replications were made for each sample. Source of dahi samples were Khan Mistanno Vandar; Krisno Mistanno Vandar; Shankar Mistanno Vandar; Misti Mokh, These samples were designated as B, C, D and E respectively. Parameters used to monitor the quality of dahi were physical, chemical and microbiological. Collected data were compiled and statistically analyzed by using one way analysis of varience (ANOVA) test by using MSTAT statistical package. It was observed that total physical score for A, B, C, D and E type of samples were 93.21±0.51, 86.98,±0.63, 78.99±0.62, 76.47±0.25 and 83.89±0.44 respectively. Statistical analysis showed that total score for A type (Lab. made) dahi was significantly (p >0.01) higher than the total score of other dahi samples. Chemical analysis showed that average fat, protein, total solids, solids not fat, ash and lactose content of A type dahi were significantly ( p > 0.01) higher than that of the B, C. D and E type dahi samples collected from different shops of Netrokona district. Microbiological analysis showed that total bacterial count, yeast and mould count of B, C, D and E type dahi samples were also significantly (p > 0.01) higher than A type dahi which was prepared in the laboratory. Although total number of coliform bacteria was lower in A type sample but there was no significant difference within different dahi samples. Judging from the results of all parameters studied it was observed that dahi samples collected from Netrokona district was inferior to dahi prepared in the Laboratory. It was also observed that quality of other four dahi samples of Netrokona was nearly similar.Bang. J. Anim. Sci. 2016. 45 (2): 60-65